2003
DOI: 10.1097/01.lab.0000093096.62765.85
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Caspase-1 in Serum Withdrawal-Induced Apoptosis of Endothelial Cells

Abstract: SUMMARY:Mouse lung endothelial cells (MLEC) and HUVEC were used under serum withdrawal (SW) conditions as a model of endothelial cell (EC) apoptosis. Apoptosis was quantified by time-lapse video microscopy. Mouse lung ECs from caspase-1 Ϫ/Ϫ mice had significantly reduced rates of SW-induced apoptosis compared with wild-type mice, specifically implicating caspase-1 in proapoptotic signaling in ECs. SW conditions induced HUVEC apoptosis with concomitant activation of caspase-1. Further studies demonstrated that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 59 publications
3
24
0
Order By: Relevance
“…Endothelial cells, of similar mesothelial origin as OSE, died by caspase-1-dependent apoptosis under serum-withdrawal conditions which cause oxidative stress (20). This evidence supports the hypothesis that reduced caspase-1a may give premalignant and malignant ovarian epithelial cells an advantage to survive under unfavorable conditions.…”
Section: Discussionsupporting
confidence: 75%
“…Endothelial cells, of similar mesothelial origin as OSE, died by caspase-1-dependent apoptosis under serum-withdrawal conditions which cause oxidative stress (20). This evidence supports the hypothesis that reduced caspase-1a may give premalignant and malignant ovarian epithelial cells an advantage to survive under unfavorable conditions.…”
Section: Discussionsupporting
confidence: 75%
“…Serum deprivation induces oxidative stress in cells as demonstrated by an excess production of ROS, such as superoxide anion, hydrogen peroxide, hydroxyl radical, and organic peroxides that can be inhibited by intracellular antioxidants (Satoh et al, 1996;King et al, 2003). We also found that trolox protects HepG2 cells from serum withdrawal-induced cell death (Fig.…”
mentioning
confidence: 48%
“…can induce reactive oxidative stress, which is believed to play an important role in cell death (Satoh et al, 1996;King et al, 2003). Fluorescence spectrophotometry was used to measure intracellular ROS production with DCFDA as the probe.…”
Section: Chx Prevents Serum Withdrawal-induced Apoptosis 1437mentioning
confidence: 99%
“…numerous reports demonstrate that serum deprivation induces programmed cell death characterized by DnA fragmentation and apoptotic bodies (6,(16)(17)(18). to investigate the correlation between Bcl-X l expression and inhibition of apoptosis caused by serum deprivation, DApI staining was used to measure apoptotic cell death.…”
Section: Resultsmentioning
confidence: 99%